2012
DOI: 10.2139/ssrn.2005352
|View full text |Cite
|
Sign up to set email alerts
|

Unemployment Risk and Wage Differentials

Abstract: Workers in less secure jobs are often paid less than identical-looking workers in more secure jobs. We show that this lack of compensating differentials for unemployment risk can arise in equilibrium when all workers are identical and firms differ only in job security (i.e. the probability that the worker is not sent into unemployment). In a setting where workers search for new positions both on and off the job, the worker's marginal willingness to pay for job security is endogenous: it depends on the behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…One of the most significant challenges faced by low‐wage workers is the risk of job loss. Research has found that low‐wage work is associated with higher job insecurity, turnover rates, and unemployment risks (de Araujo, ; Lucifora & Salverda, ; Pinheiro & Visschers, ; Stewart, ). Existing evidence also suggests that low‐wage workers have shorter job tenures (Lane, ) and that engagement in low‐wage employment can be a trap for many workers, making the transition from low‐wage work to high‐wage work difficult (Lucifora & Salverda, ; Mason & Salverda, ).…”
Section: Introductionmentioning
confidence: 99%
“…One of the most significant challenges faced by low‐wage workers is the risk of job loss. Research has found that low‐wage work is associated with higher job insecurity, turnover rates, and unemployment risks (de Araujo, ; Lucifora & Salverda, ; Pinheiro & Visschers, ; Stewart, ). Existing evidence also suggests that low‐wage workers have shorter job tenures (Lane, ) and that engagement in low‐wage employment can be a trap for many workers, making the transition from low‐wage work to high‐wage work difficult (Lucifora & Salverda, ; Mason & Salverda, ).…”
Section: Introductionmentioning
confidence: 99%
“…These involuntary employer returns accompanied by earnings losses are consistent with the evidence on J1-J2 and J2-J3 transitions presented in Tables 2 and 3. 26 Search capital also creates differentials in the probability of a job-to-job transition and in the probability of a job-to-unemployment transition. Workers who accumulate more search capital (due to more time spent in on-the-job search), have a lower probability of experiencing 26 Table 3 also shows that relatively small but positive earnings changes occur when comparing J1 earnings with J3 earnings.…”
Section: Implications For Employment Transitionsmentioning
confidence: 99%
“…Standard job ladder models assume that job destruction shocks affect all jobs equally and hence the job-tounemployment transition is independent of the number of jobs held during the employment spell. See, however, recent work byPinheiro and Visschers (2015) andJarosh (2015).…”
mentioning
confidence: 99%
“…Frictionless models such asRosen (1986) predict that wages should compensate for these values, equating utility across workers (see alsoVan Ommeren et al 2000). By highlighting the dynamic and frictional nature of the labor market, search theory has provided a framework through which the predictions for compensating differentials of these early models may be overturned (for instance,Hwang et al 1998 andBonhomme andJolivet 2009).13 Most models in this literature consider all non-wage amenities rather than focusing on one, with three exceptions beingDey and Flinn (2005), who focus on access to health care, andPinheiro and Visschers (2015) andJarosch (2016) who cosider job security.…”
mentioning
confidence: 99%